Poster: Leveraging mobile technology to support goal setting and strategies of college students - Kim, Bogoan; Rhim, So Young; Han, Kyungsik; Lee, Seok Won (UbiComp/ISWC 2018 - Adjunct Proceedings of the 2018 ACM International Joint Conference on Pervasive and Ubiquitous Computing and Proceedings of the 2018 ACM International Symposium on Wearable Computers, 2018)
The purpose of this study is to understand (1) college students' goals and the strategies needed to achieve these goals through a bottom-up approach and (2) the use of mobile technology to support such strategies. To do this, we conducted a user study with a total of 295 undergraduate and graduate students. We identified four primary goals and eight strategies. We mapped each strategy to mobile sensor data and derived specific use scenarios. By analyzing and visualizing the collected sensor data, we developed a smartphone app which is expected to help students achieve their goals.
Keywords: Bottom up approach; College life; College students; Goals; Graduate students; Mobile Technology; Smartphone app; User study; College life; Goals; Smartphone; User study